Bauhaus Principles and Reflection on Design by Women - Burcin SALTIK (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
The Bauhaus school was a revolution in itself, it had an entirely different approach to teaching students and that is what made it famous and a milestone in design education. But what is often forgotten is that apart from important men at Bauhaus, there was this group of women at Bauhaus who made innumerable contributions to making it the Bauhaus it ultimately became. They became the masters of their respective arts and this was an entire journey that displays their hard work and determination to learn. They made many artifacts not only in the women-dominated weaving workshops but also in the ceramic, wood, and metal departments. This research aims to explain Bauhaus movement, the impact of the women at Bauhaus movement, and their concept on design. The examined examples has been chosen among the valuable units in order to be clear and compare the way the supporters express their examples.